2017
DOI: 10.1002/elsc.201600246
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical characterization, cloning and molecular modeling of a digestive lipase from red seabream (Pagrus major): Structural explanation of the interaction deficiency with colipase and lipidic interface

Abstract: Biochemical characterization, cloning and molecular modeling of a digestive lipase from red seabream (Pagrus major): Structural explanation of the interaction deficiency with colipase and lipidic interfaceRed seabream digestive lipase (RsDL) was purified from fresh pyloric caeca. Pure RsDL has an apparent molecular mass of 50 kDa. The RsDL is more active on shortchain triacylglycerols (TC 4 ), and enzymatic activity decreases when medium (TC 8 ) or long-chain (olive oil) triacylglycerols were used as substrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Similarly, the BSAL also did not occur in gene duplication in mammals. In addition, the amino acid of the lid domain in pancreatic lipase was conserved in these species, it also means that the function of pancreatic lipase might be fully-functioning ( Ollis et al, 1992 ; Verger 1997 ; Smichi et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Similarly, the BSAL also did not occur in gene duplication in mammals. In addition, the amino acid of the lid domain in pancreatic lipase was conserved in these species, it also means that the function of pancreatic lipase might be fully-functioning ( Ollis et al, 1992 ; Verger 1997 ; Smichi et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the copy number of lipase genes exhibited different models between mammals and fishes. Meanwhile, the amino acid sequence analysis showed that the Ile and Leu were replaced by Ser, Lys, or Arg in the lid domain of pancreatic lipase in most fishes species, it also might influence the lipolytic ability of pancreatic lipase in fish (Smichi et al, 2017). However, the bsal gene occurred the gene duplication and obtained two to five copies in the fish species in which the Ile and Leu were absent, the phylogenetic analysis also showed that these fish species were grouped together (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The characterized enzyme shows distinct properties to TPL [8] and lipases from other marine species [19,21]. From the same family, a lipase from the red seabream has been isolated and purified and its functional properties have been performed to explain the differences with pancreatic lipases [25]. Yet, little information is available regarding structurefunction relationships of cartilaginous fish (chondrichthyans) lipases.…”
Section: Introductionmentioning
confidence: 99%